ANALISIS POTENSI SEKTORAL KABUPATEN SEMARANG - Jurni Hayati (Universitas Bengkulu, 2020)
The purpose of this study is to identify the potential sector in Semarang Regency, Jawa Tengah Province. The data used in this study were the PDRB data of the Jawa Tengah Province and the GRDP of Semarang Regency in 20015-2019 obtained from BPS of the Jawa Tengah Province. The analytical methods used are Shifshare Analysis, it can be mapped that there are potential sectors to be developed in Semarang Regency, Jawa Tengah Province. The analysis results of Shifshare show that potential sector in Semarang Regency is transportation and warehousing sector because the sector's performance is quite good, specialized, and has a competitive advantage during the 2015-2019 period. Keywords : Regional Developmen1t, Shifshare Analysis2, Potential Sectors3